Distal Radioulnar Joint Instability - Mirghasemi, Ali R. (Geriatr Orthop Surg Rehabil, 2015)
Distal radioulnar joint (DRUJ) instability is a common clinical condition but a frequently missed diagnosis. Both surgical and nonsurgical treatments are possible for chronic cases of DRUJ instability. Nonsurgical treatment can be considered as the primary therapy in less active patients, while surgery should be considered to recover bone and ligament injuries if nonsurgical treatment fails to restore forearm stability and function. The appropriate choice of treatment depends on the individual patient and specific derangement of the DRUJ